التفريخ المقاولة من الباطن كأداة لإنشاء الابتكار في قطاع النقل - زروقي, بلال; عطية, العربي (جامعة الوادي University of Eloued, 2021)
In the nineties of the last century، many hopes were placed in spin-offs by various studies to realize the weakness of the sectors that use advanced technology and innovation، for example the transport sector، the transfer of technology through classical entrepreneurship did not have the desired and expected change effect in the process of creating innovative institutions. And able to continue and develop under competition. This study explores the reasons for this relative failure and proposes spin-offs as an effective way to create institutions from the bosom of the parent institution،as this method has a special benefit in terms of valuing and using technology and transferring it from the parent institution to the spin-off institution، and searching for a way for employees on the other hand. It aspires to support the economy and the market by giving employees the freedom to choose to become entrepreneurs
spin-offs (subcontracting) as a tool for creating innovation in the transport sector
مقال
Keywords: النقل الحاضنة المؤسسة الأم الحاضنةالابتكار المؤسسة المفرخة